Analisis Implementasi Open Member Universal Health Coverage (UHC) 100% di Dinas Kesehatan Kabupaten Musi Rawas Utara Tahun 2024. - Defriansyah, Dedi; Wahyudi, Arie; Harokan, Ali; Eka Anggreny, Dian (Avicenna: Jurnal Ilmiah, 2024)
Background: The goal of Universal Health Coverage (UHC) is good and affordable health services for everyone. (Pradana, 2022). This study aims to analyze the relationship between the registration implementation mechanism, knowledge, attitudes, abilities, leadership, infrastructure, compensation, workload in North Musi Rawas Regency in 2024. Method: This type of research is a quantitative analytical survey with a cross-sectional approach. The sampling technique used is the sampling method or sampling technique. The sample in this study was the entire total population (Total Sampling) used as a research sample totaling 35 registration officers at the Health Office, Hospitals, Health Centers, and BPJS Kesehatan. The study was conducted in March-April 2024. Data collection was carried out using a questionnaire. Data were analyzed using Univariate and Bivariate. Result : Based on the results of the study variable Knowledge (p Value 0.000), Attitude (p Value 0.003), Ability (p Value 0.256), Leadership (p Value 0.365), Facilities and infrastructure (p Value 1.000), Compensation (p Value 1.000), Workload (p Value 0.677), in the Implementation of Universal Health Coverage (UHC) registration in North Musi Rawas Regency. Conclusion : There are relationship between knowledge, attitude, abilities, leadership, infrastucture, compensation, workload in the implementation of UHC registration. Keywords: Universal Health Coverage (UHC), Registration, Knowledge, Attitude